2012
DOI: 10.5200/baltica.2012.25.02
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and heavy metal distribution in the bottom sediments of the Gulf of Finland through the last decades

Abstract: Arsenic and heavy metal distribution in the bottom sediments of the Gulf of Finland through the last decades Henry ValliusVallius, H., 2012. Arsenic and heavy metal distribution in the bottom sediments of the Gulf of Finland through the last decades. Baltica, 25 (1), 23-32. Vilnius. ISSN 0067-3064.Abstract The Gulf of Finland is known to have been under rather hard stress from the anthropogenic loading of harmful substances for many decades. The emissions are known to have decreased slightly during the last tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…In this article, authors compare ABIORAS (Kaliningrad) data with the data of the Geological Survey of Finland (GTK) (Fig. 2), which methods have been reported earlier (Vallius, 2012). There was a satisfying agreement between the results of the two institutes (Fig.…”
Section: Methodsmentioning
confidence: 59%
See 3 more Smart Citations
“…In this article, authors compare ABIORAS (Kaliningrad) data with the data of the Geological Survey of Finland (GTK) (Fig. 2), which methods have been reported earlier (Vallius, 2012). There was a satisfying agreement between the results of the two institutes (Fig.…”
Section: Methodsmentioning
confidence: 59%
“…Verta et al (2009) reported that more than 30 tons of mercury was emitted to the River Kymijoki between the 1940'ies and 1971, which has been shown in many studies from the Gulf of Finland (Kokko, Turunen 1988;Vallius 2012). The concentrations of Hg in the sediments of the contaminated north-eastern part of the Gulf of Finland are very high.…”
Section: Spatial Distribution Of the Studied Elementsmentioning
confidence: 96%
See 2 more Smart Citations
“…The cooperation with the Russian and Ukrainian scientific crews worked very well, a reason why this Finnish-Russian cooperation continued until the MEP programme ended in 1995. The results of GTK work on the first MEP cruise have been reported in a couple of different papers (Vallius, Lehto 1998;Vallius 1999;Vallius 1999b;Vallius 2012;Vallius, Leivuori 1999;Vallius, Leivuori 2003).…”
Section: The Marine Ecogeological Patrol (Mep)mentioning
confidence: 99%